2014
DOI: 10.1016/j.biocel.2014.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Beta-1 integrin is important for the structural maintenance and homeostasis of differentiating fiber cells

Abstract: β1-integrin is a heterodimeric transmembrane protein that has roles in both cell-extracellular matrix and cell-cell interactions. Conditional deletion of β1-integrin from all lens cells during embryonic development results in profound lens defects, however, it is less clear whether this reflects functions in the lens epithelium alone or whether this protein plays a role in lens fibers. Thus, a conditional approach was used to delete β1-integrin solely from the lens fiber cells. This deletion resulted in two di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 74 publications
(102 reference statements)
1
26
0
Order By: Relevance
“…Scanning electron microscopy (SEM) was performed on 2–7 month old Mafg+/+:Mafk+/+ and Mafg+/−:Mafk+/− controls and Mafg−/−:Mafk+/− , Mafg+/−:Mafk−/− mutant lenses as previously described (Scheiblin et al 2014). Briefly, eyes were enucleated from mice and lenses were removed and transferred to a fixative (0.08M sodium cacodylate pH 7.4, 1.25% glutaraldehyde, 1% paraformaldehyde) (Electron Microscopy Sciences) for 48 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) was performed on 2–7 month old Mafg+/+:Mafk+/+ and Mafg+/−:Mafk+/− controls and Mafg−/−:Mafk+/− , Mafg+/−:Mafk−/− mutant lenses as previously described (Scheiblin et al 2014). Briefly, eyes were enucleated from mice and lenses were removed and transferred to a fixative (0.08M sodium cacodylate pH 7.4, 1.25% glutaraldehyde, 1% paraformaldehyde) (Electron Microscopy Sciences) for 48 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Removal of β1–integrin, another transmembrane protein able to serve as a scaffold for actin assembly, from either the entire lens or lens fibers exclusively, attenuates F-actin levels, and results in profound defects in lens fiber cell structure, although fiber cell elongation/differentiation per se proceeds normally (Scheiblin et al, 2014; Simirskii et al, 2007). Similarly, removal and/or inhibition of numerous regulators of actin cytoskeletal dynamics/organization such as Rho GTPases (Maddala et al, 2004), Rac1 GTPase (Maddala et al, 2011), tropomodulin (Nowak et al, 2009), and dystrophin (Fort et al, 2014), lead to disruptions in lens fiber cell structure without a profound effect on fiber cell elongation per se.…”
Section: Our Current Understanding Of Lens Fiber Elongationmentioning
confidence: 99%
“…Prior work on integrin function in the lens demonstrated that β1-integrins are required for both lens epithelial cell (LEC) phenotype/survival (Simirskii et al, 2007) as well as lens fiber cell structure at later stages of lens development (Scheiblin et al, 2014). However, the previous studies did not address the role of β1-integrins during early lens development.…”
Section: Resultsmentioning
confidence: 99%
“…While Le-Cre activity is first detected in the lens placode (Ashery-Padan et al, 2000), β1 integrin protein is known to have a long half-life in the lens and other tissues (Li et al, 2005; Raghavan et al, 2000; Scheiblin et al, 2014; Simirskii et al, 2007). Thus, the timing of β1-integrin protein loss in β1LE mice was determined by immunofluorescence (Figure 2A–F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation